2007
DOI: 10.1002/ijc.22578
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of C‐peptide, IGFBP‐1 and IGFBP‐2 and endometrial cancer risk; Results from the European prospective investigation into cancer and nutrition

Abstract: We conducted a case-control study nested within the European Prospective Investigation into Cancer and Nutrition, to examine the associations between prediagnostic serum concentrations of Cpeptide, insulin-like growth factor binding protein (IGFBP)-1 and IGFBP-2, and endometrial cancer risk. Among pre-and postmenopausal women, who were not currently using exogenous hormones, 286 women developed incident endometrial cancer during an average 5.1 years follow-up. Using risk set sampling, 555 matched control subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 50 publications
5
60
0
1
Order By: Relevance
“…7,8 Briefly, women who did not use exogenous hormones at blood donation, who did not report hysterectomy or who did not have a previous diagnosis of cancer (except nonmelanoma skin cancer) were eligible for the study. The 270 incident epithelial endometrial cancer cases selected included 65 cases in Denmark, 57 in Italy, 41 in Spain, 33 in the United Kingdom, 33 in the Netherlands,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Briefly, women who did not use exogenous hormones at blood donation, who did not report hysterectomy or who did not have a previous diagnosis of cancer (except nonmelanoma skin cancer) were eligible for the study. The 270 incident epithelial endometrial cancer cases selected included 65 cases in Denmark, 57 in Italy, 41 in Spain, 33 in the United Kingdom, 33 in the Netherlands,…”
Section: Methodsmentioning
confidence: 99%
“…Serum sex hormones and C-peptide had been measured previously. 7,8 Odds ratios for endometrial cancer in relation to quartiles of TNF-a or sTNFRs were calculated by conditional logistic regression. Likelihood ratio tests were used to assess linear trends in ORs with assigned quantitative scores for the quartiles (cut-off points based on the distributions of the controls).…”
Section: Short Reportmentioning
confidence: 99%
“…This is critical, given the mutual association of hyperinsulinemia and high estrogen levels with obesity. Two recent prospective investigations of endometrial cancer that lacked fasting blood specimens reported positive associations between C-peptide levels (a marker of pancreatic insulin secretion) and endometrial cancer risk (10,11), including one that also controlled for endogenous estrogen levels (10). In that study, adjustment for free estradiol levels attenuated the positive association of C-peptide with endometrial cancer.…”
Section: Introductionmentioning
confidence: 90%
“…The potential role of obesity-associated chronic hyperinsulinemia is supported by observations that high insulin levels are associated with increased endometrial cancer risk (72,73). Chronic hyperinsulinemia also increases synthesis of androgen precursors peripherally, and as elevated plasma androstenedione and testosterone concentrations increase endometrial cancer risk in pre and postmenopausal women (69), hypersulinemia may be relevant in this cancer independent of menopausal status.…”
Section: Plausible Mechanismsmentioning
confidence: 98%